Potensi Pengembangan Pariwisata Halal di Pulau Maringkik - Siti Hamdiah Rojabi; Rizal Kurniansah; Mahmudah Budiatiningsih; Ihyana Hulfa; Hasnia Minanda; Baiq Nikmatul Ulya (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
Maringkik Island is one of the small islands in Keruak District, East Lombok Regency which offers natural, cultural and artificial tourist attractions. However, tourism development on Maringkik Island has not been running massively due to concerns about the erosion of local community values and norms. So the development of halal tourism is an alternative tourism development that is in accordance with the beliefs and rules that apply to the local community. This research uses a descriptive qualitative method with data collection methods obtained through observations and interviews with the management of tourism awareness groups and the village government to explore the potential for developing Maringkik Island as a halal tourism destination as seen from the variables and dimensions of halal tourism and the availability of 4A (Attractions, Accessibility, Amenity, Ansilari) on Maringkik Island. The results of this study found that Maringkik Island needs to implement policies or rules for tourists, provide tourism options and provide facilities that support halal tourism activities from various variables and dimensions of halal tourism destinations